2001
DOI: 10.1038/sj.leu.2402284
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol, a hydroxylated analog of the chemopreventive agent resveratrol, is a potent inducer of apoptosis in the lymphoma cell line BJAB and in primary, leukemic lymphoblasts

Abstract: The stilbene phytochemicals resveratrol and piceatannol have been reported to possess substantial antitumorigenic and antileukemic activities, respectively. Although recent experimental data revealed the proapoptotic potency of resveratrol, the molecular mechanisms underlying the antileukemic activity have not yet been studied in detail. In the present study, we show that resveratrol, as well as the hydroxylated analog piceatannol, are potent inducers of apoptotic cell death in BJAB Burkittlike lymphoma cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
119
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 46 publications
0
119
0
3
Order By: Relevance
“…2D). Piceatannol has been shown to inhibit cell viability and to induce apoptosis in various cell types such as macrophages (42), prostate cancer cells (43), adrenal pheochromocytoma cells (44), lymphoblasts (45), and neutrophils (46). However, our result showed that the viability of the differentiating 3T3-L1 cells was not significantly influenced by piceatannol treatment up to concentration of 100 M (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2D). Piceatannol has been shown to inhibit cell viability and to induce apoptosis in various cell types such as macrophages (42), prostate cancer cells (43), adrenal pheochromocytoma cells (44), lymphoblasts (45), and neutrophils (46). However, our result showed that the viability of the differentiating 3T3-L1 cells was not significantly influenced by piceatannol treatment up to concentration of 100 M (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Piceatannol not only inhibits protein tyrosine kinase Syk but also interferes with other kinases and induces apoptosis in leukemic lymphoblasts. 66,67 TEL-Syk fusion is a useful tool in the search for another Syk-specific inhibitor and for future investigation of Syk.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial apoptosis is the most prominent intrinsic apoptosis signalling pathway (for reviews, see, Calicheamicin activates mitochondria via caspases and Bax A Prokop et al Kroemer and Reed, 2000;Martinou and Green, 2001). It is triggered by various cytotoxic drugs such as taxol or epirubicin (Wieder et al, 2001a;von Haefen et al, 2003), natural compounds such as piceatannol (Wieder et al, 2001b), truncated ceramides or ionizing radiation . In a first series of experiments, we demonstrated that challenge with calicheamicin led to a dramatic decrease of the mitochondrial membrane potential, which was observed in approximately 80% of BJAB cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the apoptotic program may be triggered by various, unphysiological death stimuli, for example, ionizing radiation , chemotherapeutic anticancer drugs (Engels et al, 2000;Wieder et al, 2001a) and by natural compounds (Wieder et al, 2001b). So far, three major pathways of apoptotic cell death have been defined: (i) the death receptor-mediated signalling cascade , (ii) the mitochondrial pathway involving the apoptosome (Daniel, 2000;Rudner et al, 2001), and (iii) the endoplasmic reticulum-dependent stress response (Belka and Budach, 2002;Rudner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%